Tower generic data processing - Necco, Claudia Mónica (2005)
Many aspects of data processing are functional in nature and can take advantage of recent developments in the area of functional programming and calculi. The work described in this paper is an attempt to contribute to this line of thought, in particular exploiting the Haskell functional language as support tool. Haskell is used mainly to animate an abstract model of the relational database calculus as defined by Maier, written in the style of model-oriented formal specification. Parametricity and genericity (polytypism) make room for generic versions of relational standard (type-constructor parametric) and multi-dimensional analysis operations are expressed in Generic Haskell. Besides animation, the functional model is further subjected to formal reasoning and calculation, paving the way to the eventual polytypic (generic) formulation of the standard relational calculus.